Femoral Pseudoaneurysms (Latakia University Journal -Medical Sciences Series, 2021)
Treatment of postcatheterization femoral false aneurysms. The incidence of iatrogenic femoral false aneurysms has risen dramatically in recent years and is estimated at %0.5 for diagnostic procedures and may rise to %9 or more for therapeutic procedures. This increased incidence is related to the increased number of arterial punctures performed for diagnostic or therapeutic purposes and their major complexity and duration. Risk factors for the development of iatrogenic false aneurysms include operator inexperience, age greater than 60, female gender, catheter size greater than 8F and concurrent anticoagulation.Prevention of false aneurysms is based upon an atraumatic arterial puncture, good compression therapy after sheath removal and use of percutaneous arterial closure devices. Contrarily to the arterial lesions following severe injuries, the natural course of false aneurysms is quite benign with spontaneous occlusion in the majority of cases. Therefore, a mandatory surgical approach is no longer advocated and alternative therapeutic options have been proposed. These include sonographic surveillance, compression ultrasonography, percutaneous thrombin or coil embolization.Surgery is still clearly indicated in presence of local nervous or venous compression, associated homolateral lower limb ischemia, great size of the aneurysm, and unsuccessful non-invasive treatment. Sonographic surveillance has shown to be safe in hospitalized or ambulatory patients. However, fear of aneurysm rupture and cost of repeated ultrasonographic exams preclude widespread utilization. Compression ultrasonography is safe and effectiveness varies between 70 and %100, according to studies. Compression ultrasonography may be painful, has often to be associated with mild analgesia, is time consuming and less effective in presence of concurrent anticoagulation. Thrombin injection seems particularly effective, is painless and has a limited rate of complications in expert hands.Severe anaphylactic reactions and severe coagulopathy in reexposed patients have been described and represent clear contra-indications to thrombin injection. Coil embolization of the false aneurysm is as effective as thrombin injection and is reported in a limited number of patients.There is no formal consensus about treatment of the vast majority of non-surgical false aneurysms. In an absence of stringent indication to surgical approach, compression ultrasonography may be used first as it is widely available, and does not require highly specialized skills. Compression therapy should be done after a transient interruption of anticoagulant treatment, if allowed by clinical context.If compression therapy fails, percutaneous injection of thrombin or coil embolization are effective and associated with a low complication rate. However, these techniques are less widely available and necessitate an experienced operator. As recurrences have been described with each of these techniques, every non-surgically treated false aneurysm should be monitored for 24 hour with ultrasonographycontrol to ensure effective thrombosis. (J Mal Vasc 2004 29: 63-72)